2016
DOI: 10.1088/0031-9155/61/16/6181
|View full text |Cite
|
Sign up to set email alerts
|

Inverse 4D conformal planning for lung SBRT using particle swarm optimization

Abstract: A critical aspect of highly potent regimens such as lung stereotactic body radiation therapy (SBRT) is to avoid collateral toxicity while achieving planning target volume (PTV) coverage. In this work, we describe four dimensional conformal radiotherapy (4D CRT) using a highly parallelizable swarm intelligence-based stochastic optimization technique. Conventional lung CRT-SBRT uses a 4DCT to create an internal target volume (ITV) and then, using forward-planning, generates a 3D conformal plan. In contrast, we i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 19 publications
(31 citation statements)
references
References 64 publications
1
30
0
Order By: Relevance
“… and as quadratic differences in Ref. ). The DVH dose coverage deviation from prescription dose DiP for a given prescription cumulative volume is given by ftargetDVH=1Nvoxels,ifalse∑j=1Nvoxels,ifalse|DiPDi,jfalse|θfalse(DiPDi,jfalse),where the θ ( h ) is the Heaviside function defined by θfalse(hfalse)=1ifh00otherwise. Nvoxels,i is the number of voxels of the i th structure, and j is the index of voxels.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“… and as quadratic differences in Ref. ). The DVH dose coverage deviation from prescription dose DiP for a given prescription cumulative volume is given by ftargetDVH=1Nvoxels,ifalse∑j=1Nvoxels,ifalse|DiPDi,jfalse|θfalse(DiPDi,jfalse),where the θ ( h ) is the Heaviside function defined by θfalse(hfalse)=1ifh00otherwise. Nvoxels,i is the number of voxels of the i th structure, and j is the index of voxels.…”
Section: Methodsmentioning
confidence: 99%
“…It has been reported that DVH‐based objective functions show nonconvex behavior . MCO based on convex geometrical approximations has been tested clinically and it was reported that the navigated plans show discrepancies from the optimal deliverable plans .…”
Section: Introductionmentioning
confidence: 99%
“…Beam dose deposition matrices were calculated in Eclipse Treatment Planning System (V13.6, Varian Medical Systems, Palo Alto, CA) using the Anisotropic Analytical Algorithm (AAA) and exported into our in-house PSO engine for inverse planning. 31,32 The optimization task was to minimize the risk-based objective function. We employed apertures that were preconfigured by Eclipse and optimized the corresponding MU weights.…”
Section: B1 Inverse Planningmentioning
confidence: 99%
“…We used inverse planning and particle swarm optimization (PSO), a highly parallelized, metaheuristic, global optimization algorithm, to minimize our modeled overall risk. PSO has been customized and successfully used in various other RT inverse planning studies with nonconvex solution spaces . We allowed the optimization algorithm to choose among a large set of gantry angles that included, but was not limited to, the beam angles routinely used in clinical practice.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation